Mat materials and holding and sealing materials

A laminated mat material with oriented and random inorganic fiber layers and controlled binder distribution enhances tensile strength and friction, addressing breakage issues during wrapping and ensuring proper alignment with exhaust gas treatment bodies in purification devices.

JP7606027B1Active Publication Date: 2024-12-24IBIDEN CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024053411
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-28
Publication Date
2024-12-24
Estimated Expiration
2044-03-28

AI Technical Summary

Technical Problem

Existing mat materials used in exhaust gas purification devices lack sufficient tensile strength, leading to potential breakage during wrapping around exhaust gas treatment bodies due to applied tensile loads.

Method used

A laminated mat material comprising alternating layers of oriented and random inorganic fiber layers, with a higher binder content in the outermost layers, enhances tensile strength and frictional force, preventing misalignment and breakage.

Benefits of technology

The laminated mat material with oriented and random layers provides high tensile strength and reduced elongation, effectively preventing breakage during wrapping and ensuring proper alignment with exhaust gas treatment bodies, while maintaining binder content within acceptable limits for high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606027000001_ABST
    Figure 0007606027000001_ABST
Patent Text Reader

Abstract

To provide a mat material having high tensile strength to solve the problem of the mat material breaking when wrapped around an exhaust gas treatment body. The laminated mat (20) includes at least one layer each of an orientation layer (30) made of inorganic fibers in which the orientation direction of the inorganic fibers is uniform, and a random layer (40) made of inorganic fibers in which the orientation direction of the inorganic fibers is random. The laminated mat is a mat material (10) that includes a binder for increasing frictional force when wrapped around an exhaust gas treatment body.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a mat material and a holding sealing material. [Background technology]

[0002] Exhaust gas emitted from internal combustion engines such as diesel engines contains particulate matter (hereinafter referred to as PM), and in recent years, the harm that this PM poses to the environment and human body has become a problem. In addition, exhaust gas also contains harmful gas components such as CO, HC, and NOx, and there are concerns about the impact that these harmful gas components have on the environment and human body.

[0003] In response to this, various exhaust gas purification devices have been proposed that capture PM in exhaust gas and purify harmful gas components, and are composed of an exhaust gas treatment body made of porous ceramics such as silicon carbide and cordierite, a metal casing that houses the exhaust gas treatment body, and a retaining seal material (mat material) disposed between the exhaust gas treatment body and the metal casing. The main purpose of the retaining seal material (mat material) is to prevent the exhaust gas treatment body from coming into contact with the metal casing that covers its outer periphery and being damaged by vibrations and impacts caused by the running of the automobile, and to prevent exhaust gas from leaking from between the exhaust gas treatment body and the metal casing.

[0004] As an example of a mat material used for such applications, Patent Document 1 discloses a holding and sealing material consisting of a mat of a predetermined thickness containing inorganic fibers whose surface is covered with a binder layer, wherein the binder layer contains an organic binder and an inorganic binder, and wherein when the mat is divided into three equal parts in the thickness direction into a first surface portion, a central portion, and a second surface portion, the amount of organic binder attached to the first surface portion is greater than the amount of organic binder attached to the central portion and is also greater than the amount of organic binder attached to the second surface portion. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2015-63925 A Summary of the Invention [Problem to be solved by the invention]

[0006] When wrapping the mat material around the exhaust gas treatment body, the wrapping operation may be performed while applying a tensile load to the mat material. If the tensile strength of the mat material is low during this operation, the mat material may break due to the tensile load, which is a problem. The mat material described in Patent Document 1 also has insufficient tensile strength, and there has been a demand for improving the tensile strength of the mat material.

[0007] The present invention has been made in consideration of the above problems, and has an object to provide a mat material having high tensile strength. [Means for solving the problem]

[0008] The mat material of the present invention includes a laminated mat including at least one orientation layer made of inorganic fibers in which the orientation direction of the inorganic fibers is uniform, and at least one random layer made of inorganic fibers in which the orientation direction of the inorganic fibers is random, The laminate mat is a mat material containing a binder.

[0009] The laminated mat constituting the mat material of the present invention includes an orientation layer and a random layer. The presence of the orientation layer makes it possible to obtain a mat material that is less likely to stretch and has high tensile strength. In addition, the random layer is easily impregnated with a binder. By incorporating a binder into the mat material, the frictional force of the surface of the mat material can be increased.

[0010] In the mat material of the present invention, the orientation layers and the random layers are laminated alternately in the thickness direction, and it is preferable that the random layers are disposed on both of the two outermost layers of the laminate mat.

[0011] When the binder is impregnated into the laminate mat, the random layer is placed on the outermost layer of the laminate mat, and the binder is allowed to penetrate in the thickness direction of the laminate mat. Since the random layer is easily permeated by the binder and the oriented layer is difficult for the binder to permeate, the binder is blocked in the thickness direction of the laminate mat by the oriented layer. As a result, the binder content is high in the outermost layer of the laminated mat with which the binder liquid for binder impregnation comes into contact. Since a high binder content increases frictional force, if the outermost layer with a high binder content is used as the surface that contacts the exhaust gas treatment body, which requires frictional force during winding, the mat material can be preferably used because it prevents slippage between the exhaust gas treatment body and the mat material.

[0012] In the mat material of the present invention, the laminate mat preferably contains at least one of an organic binder and an inorganic binder.

[0013] In the mat material of the present invention, when the laminated mat is divided into three equal parts in the thickness direction into a first surface portion, a central portion, and a second surface portion, the random layer is disposed on the outermost layer of the first surface portion, It is preferable that the content of the binder in the first surface portion is greater than the content of the binder in the central portion and greater than the content of the binder in the second surface portion.

[0014] In the above-mentioned mat material, since the binder content is high in the first surface portion, when the first surface portion is used as the portion that contacts the exhaust gas treatment body, the mat material is prevented from shifting from the exhaust gas treatment body, and the mat material can be preferably used. In addition, the mat material is used in exhaust gas purification equipment, but the environment in which the exhaust gas purification equipment is used is a high-temperature environment, and the binder (especially the organic binder) may volatilize. Therefore, mat materials expected to be used in exhaust gas purification equipment are required not to contain a large amount of binder. In the above mat material, the binder content is increased in the first surface portion, but not in the entire mat material, so that the requirement regarding the binder content of the entire mat material can be satisfied.

[0015] In the mat material of the present invention, it is preferable that the content of the binder satisfies the following relationship. 0.4≦(center / first surface) 0.2≦(second surface portion / first surface portion) (Second surface / center)≦0.5 It is also preferable that the content of the binder further satisfies the following relationship. 0<(Second surface / center)

[0016] When the binder content in the first surface portion, the central portion, and the second surface portion satisfies the above relationship, when the first surface portion is brought into contact with and wrapped around the exhaust gas treatment body, the frictional force between the mat material and the exhaust gas treatment body is improved, and interfacial slippage is less likely to occur between the mat material and the exhaust gas treatment body when the mat material is assembled into the casing.

[0017] In the mat material of the present invention, it is preferable that the inorganic fibers in the alignment layer contain 70% or more of inorganic fibers having an inclination of 60 to 90 degrees with respect to the width direction of the mat material.

[0018] In the mat material of the present invention, it is preferable that the tensile strength at break measured by a tensile test is 200 kPa or more. In addition, the elongation at break measured by a tensile test is preferably 3.5 mm or less.

[0019] When the tensile strength at break and the elongation at break measured by the tensile test are within the above ranges, breakage of the mat material during wrapping around an exhaust gas treatment unit or the like can be more reliably prevented. Furthermore, if the tensile strength at break is high and the elongation at break is small, the variation in workability during winding is reduced.

[0020] The holding seal material of the present invention is made of the mat material of the present invention and is used to hold an exhaust gas treating body in an exhaust gas purification apparatus.

[0021] The mat material of the present invention is a mat material that is difficult to stretch and has high tensile strength, so that it is difficult to break when wrapped around an exhaust gas treatment body, and is therefore suitable for use as a holding and sealing material. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is a perspective view that illustrates an example of the mat member. [Diagram 2] FIG. 2 is a cross-sectional view of the mat material shown in FIG. 1 taken along the line AA. [Diagram 3] FIG. 3 is a perspective view that illustrates an example of the alignment layer. [Figure 4] FIG. 4 is an example of a micrograph including inorganic fibers. [Diagram 5] FIG. 5 is a perspective view illustrating a schematic example of a random layer. [Figure 6] FIG. 6 is a cross-sectional view that illustrates a needle mat including a rivet portion. [Figure 7] FIG. 7 is a cross-sectional view that illustrates an example of an exhaust gas purification device. [Figure 8] FIG. 8 is a perspective view that illustrates an example of an exhaust gas treating body that constitutes an exhaust gas purification device. [Figure 9] FIG. 9 is a perspective view that typically shows an example of a method for producing an exhaust gas purification device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] An example of the mat material and the holding sealing material of the present invention will be described in detail below with reference to the drawings. FIG. 1 is a perspective view that illustrates an example of the mat member. FIG. 2 is a cross-sectional view of the mat material shown in FIG. 1 taken along the line AA. The mat material 10 shown in FIG. 1 is a laminated mat 20 including an orientation layer 30 and a random layer 40 . Three layers, a random layer 40a, an orientation layer 30, and a random layer 40b, are laminated along the thickness direction (the direction indicated by the double-headed arrow T in Figs. 1 and 2) of the laminate mat 20. The random layer 40a and the random layer 40b are layers of the same specifications.

[0024] The laminate mat 20 is a mat that is long in its longitudinal direction (the direction indicated by the double-headed arrow L in FIG. 1). The laminate mat 20 has two main surfaces, a first main surface 23 and a second main surface 24. The first main surface 23 is the surface of the random layer 40a, and the second main surface 24 is the surface of the random layer 40b.

[0025] The laminate mat 20 has four side surfaces, and the side surfaces along the longitudinal direction of the laminate mat 20 are a first long side surface 25 and a second long side surface 26. In addition, the side surfaces along the width direction of the laminate mat 20 (the direction indicated by the double-headed arrow W in FIG. 1) are a first short side surface 27 and a second short side surface 28. The laminated mat 20 has a generally rectangular shape when viewed from above, with a concave portion formed on the first short side surface 27 and a convex portion formed on the second short side surface 28. The concave portion and the convex portion are shaped to fit together exactly when the mat material is wrapped around an exhaust gas purification device, an exhaust gas treatment body, or an exhaust pipe having a cylindrical outer periphery. In the mat member of this embodiment, the shapes of the mating portions are recessed and protruding, but the shapes of the mating portions may be an L-shaped combination.

[0026] FIG. 3 is a perspective view that illustrates an example of the alignment layer. FIG. 3 shows an orientation layer 30, and illustrates inorganic fibers 31 constituting the orientation layer 30, together with their orientation direction. The orientation layer 30 is made of inorganic fibers and has the inorganic fibers oriented in the same direction. In the orientation layer shown in Fig. 3, the inorganic fibers are oriented in the longitudinal direction of the mat material.

[0027] In this specification, "the orientation direction of inorganic fibers is uniform" means that when the angle of the inorganic fibers is measured in one direction of the photographed area (usually the horizontal direction of the photographed area) in a microscopic photograph containing inorganic fibers, 50% or more of the fibers are in the range of 75 to 90 degrees.

[0028] FIG. 4 is an example of a micrograph including inorganic fibers. Inorganic fibers 31 are shown in the photograph shown in Fig. 4. It can be seen from Fig. 4 that many of the inorganic fibers are oriented in the vertical direction (90° direction) of the photographed area. In addition, 52% of the inorganic fibers have an angle θ of 75 to 90 degrees measured with respect to the horizontal direction (0° direction) of the photographed area. That is, the layer from which the photograph shown in FIG. 4 was taken is the alignment layer.

[0029] In addition, it is preferable that the inorganic fibers in the alignment layer contain 70% or more of inorganic fibers having an inclination of 60 to 90 degrees with respect to the width direction of the mat material. When the orientation layer satisfies the above conditions, the direction in which tensile stress is applied when the mat material is wrapped and the orientation of the inorganic fibers are aligned, which is preferable because the tensile strength of the mat material tends to be high. The horizontal direction of the photograph shown in FIG. 4 is the width direction of the mat material, and 78% of the inorganic fibers have an angle θ in the range of 60 to 90 degrees. That is, in the orientation layer from which the photograph shown in FIG. 4 was taken, 70% or more of the inorganic fibers are inclined at an angle of 60 to 90 degrees with respect to the width direction of the mat material. A direction inclined at 60 to 90 degrees with respect to the width direction of the mat material can be said to be a direction along the longitudinal direction of the mat material, and therefore the inorganic fibers in the orientation layer can be said to be oriented along the longitudinal direction of the mat material.

[0030] In the orientation layer, the ratio of inorganic fibers having an angle θ of 75 to 90 degrees measured with respect to the horizontal direction (0° direction) of the photographed area may be 60% or more, or 70% or more, and the ratio of inorganic fibers having an angle θ of 75 to 90 degrees may be 90% or less, or 80% or less.

[0031] The orientation layer may contain 75% or more, or 85% or more, of inorganic fibers having an inclination of 60 to 90 degrees with respect to the width direction of the mat material, and may contain 95% or less, or 90% or less, of inorganic fibers having an inclination of 60 to 90 degrees with respect to the width direction of the mat material.

[0032] FIG. 5 is a perspective view illustrating a schematic example of a random layer. FIG. 5 shows a random layer 40, and the inorganic fibers 41 that constitute the random layer 40 are shown in schematic form. The random layer 40 is made of inorganic fibers, and the inorganic fibers are randomly oriented.

[0033] In this specification, "the orientation direction of inorganic fibers is random" means that in a micrograph containing inorganic fibers, it is visible that the inorganic fibers are not oriented in a specific direction in the photographed area. A layer in which the orientation of inorganic fibers does not meet the above definition of an oriented layer may be called a random layer.

[0034] The oriented layer and the random layer in the laminate mat are preferably arranged alternately in the thickness direction. In Fig. 1 and Fig. 2, they are arranged alternately in the order of random layer 40a / oriented layer 30 / random layer 40b, and the random layer is arranged in both of the two outermost layers of the laminate mat. The number of mats laminated in the laminate mat is not particularly limited as long as it contains at least one oriented layer and at least one random layer. Since it is preferable that the random layer is arranged as the outermost layer and the random layer and the oriented layer are arranged alternately, it is preferable that the number of mats is 3 or 5. Examples include a 3-layer structure of random layer / oriented layer / random layer, and a 5-layer structure of random layer / oriented layer / random layer / oriented layer / random layer.

[0035] The mat constituting the laminated mat contains inorganic fibers. The inorganic fibers are not particularly limited and may be alumina fibers, silica fibers, etc. Also, they may be glass fibers or biosoluble fibers. They may be changed according to the properties required for the mat material, such as heat resistance and wind erosion resistance, and it is preferable to use fibers with a large diameter and fiber length that can comply with the environmental regulations of each country.

[0036] Among these, inorganic fibers of low crystalline alumina are preferred, inorganic fibers of low crystalline alumina having a mullite composition are more preferred, and inorganic fibers containing a spinel type compound are even more preferred.

[0037] In the mat material of the present invention, the laminated mat contains a binder. By incorporating a binder into the mat material, the frictional force of the surface of the mat material can be increased. Since the random layer is easily impregnated with the binder, it is preferable to impregnate the random layer with the binder.

[0038] The lamination mat preferably contains at least one of an organic binder and an inorganic binder. By adding a binder to the laminated mat, the frictional force of the mat material can be increased.

[0039] Examples of the organic binder include rubber-based resins, styrene-based resins, silicone-based resins, acrylic-based resins, polyester-based resins, and polyurethane resins.

[0040] The inorganic binder may be an inorganic sol dispersion (alumina sol, silica sol, zirconia sol, titania sol, etc.).

[0041] The content of the binder (total amount of organic binder and inorganic binder) in the laminate mat is preferably 0.2% by weight or more and 30% by weight or less based on the weight of the laminate mat. When an organic binder is included, the content of the organic binder is preferably 0.1% by weight or more and 20% by weight or less, and when an inorganic binder is included, the content of the inorganic binder is preferably 0.1% by weight or more and 10% by weight or less.

[0042] When the lamination mat contains a binder, it is preferred that the outermost layer of the lamination mat is a random layer, and an orientation layer is disposed inside the random layer. When the binder is impregnated into the laminate mat, the random layer is placed on the outermost layer of the laminate mat, and the binder is allowed to penetrate in the thickness direction of the laminate mat. Since the random layer is easily permeated by the binder and the oriented layer is difficult for the binder to permeate, the binder is blocked in the thickness direction of the laminate mat by the oriented layer. As a result, the binder content is high in the outermost layer of the laminated mat with which the binder liquid for binder impregnation comes into contact. Since a high binder content increases frictional force, if the outermost layer with a high binder content is used as the surface that contacts the exhaust gas treatment body, which requires frictional force during winding, the mat material can be preferably used because it prevents slippage between the exhaust gas treatment body and the mat material.

[0043] As a specific example of a configuration in which the outermost layer of the laminate mat is a random layer and an orientation layer is disposed inside the random layer, it is preferable that the orientation layer and the random layer are laminated alternately in the thickness direction and that both of the two outermost layers of the laminate mat are random layers.

[0044] Furthermore, when the laminated mat is divided into three equal parts in the thickness direction into a first surface portion, a central portion, and a second surface portion, it is preferable that a random layer is disposed in the outermost layer of the first surface portion, and that the binder content in the first surface portion is greater than the binder content in the central portion and is also greater than the binder content in the second surface portion.

[0045] In the laminate mat 20 shown in the cross-sectional view of Fig. 2, the random layer 40a, the orientation layer 30, and the random layer 40b are all the same thickness, so that the random layer 40a can be regarded as the first surface portion, the orientation layer 30 as the center portion, and the random layer 40b as the second surface portion. In this case, it is preferable that the binder content in the random layer 40a is greater than the binder content in the orientation layer 30 and greater than the binder content in the random layer 40b.

[0046] In a mat material having a random layer arranged on the outermost layer of the first surface portion, the binder content in the first surface portion is high, so when the first surface portion is used as the portion that contacts the exhaust gas treatment body, misalignment between the exhaust gas treatment body and the mat material is prevented, and the mat material can be preferably used. In addition, the mat material is used in exhaust gas purification equipment, but the environment in which the exhaust gas purification equipment is used is a high-temperature environment, and the binder (especially the organic binder) may volatilize. Therefore, mat materials expected to be used in exhaust gas purification equipment are required not to contain a large amount of binder. In the mat material having the above-mentioned configuration, the binder content is increased in the first surface portion, but the content of the mat material is not increased in the entire mat material, so that the requirement regarding the binder content of the entire mat material can be satisfied.

[0047] In addition, it is preferable that the content of the binder satisfies the following relationship. 0.4≦(center / first surface) 0.2≦(second surface portion / first surface portion) (Second surface / center)≦0.5 Furthermore, it is preferable that the binder content satisfies the following relationship. 0<(Second surface / center)

[0048] When the binder content in the first surface portion, the central portion, and the second surface portion satisfies the above relationship, when the first surface portion is brought into contact with and wrapped around the exhaust gas treatment body, the frictional force between the mat material and the exhaust gas treatment body is improved, and interfacial slippage is less likely to occur between the mat material and the exhaust gas treatment body when the mat material is assembled into the casing.

[0049] In addition, it is preferable that the binder content of the first surface portion is 0.1 wt % or more and 29.0 wt % or less, the binder content of the central portion is 0.2 wt % or more and 15.0 wt % or less, and the binder content of the second surface portion is 0.05 wt % or more and 5.0 wt % or less.

[0050] In the mat material of the present invention, the tensile strength at break measured by a tensile test is preferably 200 kPa or more. In addition, the elongation at break measured by a tensile test is preferably 3.5 mm or less.

[0051] The tensile strength at break and the elongation at break are measured by cutting the mat material into a sample having a length of 200 mm along the longitudinal direction of the mat material and a width of 50 mm along the width direction of the mat material. The thickness of the sample is measured at three points, and using a universal testing machine equipped with a chuck (gripping jig) for tensile tests, the chuck distance is set to 40 mm on one side, and the mat material is pulled in the longitudinal direction of the sample at a speed of 100 mm / min. The load and pulling distance at the time of break are determined. Tensile strength at break is calculated as follows: Tensile strength at break = load at break / (sample thickness x width). The pulling distance at break is defined as the elongation at break.

[0052] When the tensile strength at break and the elongation at break measured by the tensile test are within the above ranges, breakage of the mat material during wrapping around an exhaust gas treatment unit or the like can be more reliably prevented. Furthermore, if the tensile strength at break is high and the elongation at break is small, the variation in workability during winding is reduced.

[0053] The orientation layer and random layer constituting the laminated mat may be a papermaking mat obtained by a papermaking method, or a needle mat obtained by a needling method.

[0054] In the case of the papermaking method, for example, inorganic fibers such as alumina fibers and silica fibers, an inorganic binder, and water are mixed so that the content of inorganic fibers in the raw material liquid is a predetermined value, and the mixture is stirred with a stirrer to prepare a slurry containing inorganic fibers. The slurry may contain a colloidal solution made of a polymer compound or a resin, as necessary. Next, the mixed liquid is poured into a molding machine having a filtration mesh formed on the bottom surface, and the water in the mixed liquid is dehydrated through the mesh to produce a raw material sheet. Then, the raw material sheet is heated and compressed under predetermined conditions to obtain a papermaking mat.

[0055] In the case of the needling method, for example, a spinning mixture made of a basic aluminum chloride aqueous solution, silica sol, or the like is spun by a blowing method to produce an inorganic fiber precursor having an average fiber diameter of 3 to 10 μm. Next, the inorganic fiber precursor is compressed to produce a continuous sheet-like product of a predetermined size, which is subjected to a needling treatment (needle punching treatment), and then subjected to a firing treatment to obtain a needle mat.

[0056] The method for producing the orientation layer and the random layer is not particularly limited, but the following method can be mentioned, for example. When the orientation layer is produced by a papermaking method, a slurry containing inorganic fibers is papered and allowed to flow in one direction, whereby the fibers are oriented in the direction of flow, thereby forming an orientation layer. When a random layer is produced by a papermaking method, a slurry containing inorganic fibers is poured into a mold from above. Since there is no flow of the slurry, the fibers do not orient in a specific direction, resulting in a random layer. The slurry containing inorganic fibers may contain at least one of an organic binder and an inorganic binder.

[0057] The laminated mat may also be a paper-made mat obtained by laminating an orientation layer and a random layer and then subjecting them to a needling treatment.

[0058] A binder may be applied to the laminate mat. When a binder is applied to the laminate mat, a binder liquid containing a binder is made to permeate the laminate mat in the thickness direction from one main surface (first main surface) of the laminate mat. The penetration of the binder liquid may be performed by a method such as curtain coating, in which the binder liquid is dropped onto the mat to apply the binder liquid to the inorganic fibers in the mat, or by a method such as spray coating, in which the binder liquid is sprayed onto the mat.

[0059] When a random layer is placed as the outermost layer of a laminate mat and an oriented layer is placed inside it, the binder easily penetrates into the random layer but does not easily penetrate into the oriented layer, so that the binder is blocked by the oriented layer in the thickness direction of the laminate mat. As a result, the binder content is high in the outermost layer of the laminated mat with which the binder liquid for binder impregnation comes into contact. Since a high binder content increases frictional force, if the outermost layer with a high binder content is used as the surface that contacts the exhaust gas treatment body, which requires frictional force during winding, the mat material can be preferably used because it prevents slippage between the exhaust gas treatment body and the mat material.

[0060] It is also preferable that the needle mat contains a binder, and has a rivet portion that extends in the thickness direction along the needle marks from the first main surface of the laminate mat and has a higher binder concentration than other portions.

[0061] FIG. 6 is a cross-sectional view that illustrates a needle mat including a rivet portion. FIG. 6 shows rivet portions 51 formed by impregnating needle marks 50 formed by needling processing from the first main surface 23 of the laminate mat 20 with a binder. When the needle mat has rivet portions, the permeation of the binder proceeds in the thickness direction of the mat material, which causes binding between the inorganic fibers, leading to structural reinforcement of the mat material, which is preferable. The rivet portion is a portion where the binder (organic binder) is scorched by heating the mat material, and the scorched binder appears like a rivet in the cross section of the laminated mat. The depth of the rivet portion is not particularly limited. FIG. 6 also shows that needle marks 50 are present on the second main surface 24 of the laminate mat 20, but no rivet portions are present because the binder has not penetrated from the second main surface 24.

[0062] The mat material of the present invention can be used as a holding and sealing material that is used to hold an exhaust gas treatment body in an exhaust gas purification apparatus. The holding seal material of the present invention comprises the mat material of the present invention, and is used as a holding seal material for holding an exhaust gas treating body in an exhaust gas purification apparatus.

[0063] FIG. 7 is a cross-sectional view that illustrates an example of an exhaust gas purification device. As shown in FIG. 7, the exhaust gas purification device 100 includes a metal casing 130, an exhaust gas treatment body 120 housed in the metal casing 130, and a mat material 10 which is a retaining sealing material disposed between the exhaust gas treatment body 120 and the metal casing 130. The exhaust gas treatment body 120 is a columnar structure in which a large number of cells 125 are arranged in parallel in the longitudinal direction with cell walls 126 separating them. Note that, to the ends of the metal casing 130, an inlet pipe for introducing exhaust gas discharged from the internal combustion engine and an outlet pipe for discharging exhaust gas that has passed through the exhaust gas purification device to the outside are connected as necessary.

[0064] A case where exhaust gas passes through the exhaust gas purification device 100 having the above-mentioned configuration will be described below with reference to FIG. As shown in Fig. 7, exhaust gas discharged from an internal combustion engine and flowing into the exhaust gas purification device 100 (in Fig. 7, the exhaust gas is indicated by G, and the flow of the exhaust gas is indicated by arrows) flows into one cell 125 opening at the exhaust gas inlet end face 120a of the exhaust gas treatment body (honeycomb filter) 120, and passes through a cell wall 126 separating the cells 125. At this time, PM in the exhaust gas is captured by the cell wall 126, and the exhaust gas is purified. The purified exhaust gas flows out from the other cell 125 opening at the exhaust gas outlet end face 120b, and is discharged to the outside.

[0065] In the exhaust gas purification device 100 shown in Figure 7, the retaining sealing material is the mat material 10 of the present invention, and the first main surface 23 of the laminated mat constituting the mat material 10 is arranged on the side of the exhaust gas treatment body 120, and the second main surface 24 is arranged on the side of the metal casing 130.

[0066] The material of the metal casing constituting the exhaust gas purification device is not particularly limited as long as it is a heat-resistant metal, and specific examples thereof include metals such as stainless steel, aluminum, and iron.

[0067] The shape of the casing may be a substantially cylindrical shape, a clamshell shape, or a substantially elliptical or polygonal shape in cross section.

[0068] FIG. 8 is a perspective view that illustrates an example of an exhaust gas treating body that constitutes an exhaust gas purification device.

[0069] The exhaust gas treatment body 120 shown in Fig. 8 is a honeycomb structure made of a columnar ceramic material in which a large number of cells 125 are arranged in parallel in the longitudinal direction with cell walls 126 between them. Either end of the cells 125 is sealed with a plug 128. A peripheral coating layer 127 is provided on the outer periphery of the honeycomb structure for the purposes of reinforcing the outer periphery of the honeycomb structure, arranging the shape, and improving the heat insulation of the honeycomb structure.

[0070] When either end of the cells 125 is sealed, it is preferable that, when viewed from one end of the exhaust gas treatment body 120, cells with sealed ends and cells without sealing are arranged alternately.

[0071] The cross-sectional shape of the exhaust gas treatment body 120 cut in a direction perpendicular to the longitudinal direction is not particularly limited, and may be approximately circular, approximately elliptical, or approximately polygonal, such as approximately triangular, approximately rectangular, approximately pentagonal, or approximately hexagonal.

[0072] The cross-sectional shape of the cells 125 constituting the exhaust gas treatment body 120 may be a substantially polygonal shape such as a substantially triangular shape, a substantially rectangular shape, a substantially pentagonal shape, a substantially hexagonal shape, or a substantially circular shape or a substantially elliptical shape. The exhaust gas treatment body 120 may be a combination of cells having a plurality of cross-sectional shapes.

[0073] The material constituting the exhaust gas treatment body 120 is not particularly limited, but non-oxides such as silicon carbide and silicon nitride, and oxides such as cordierite and aluminum titanate can be used. Among these, it is particularly desirable to use non-oxide porous fired bodies such as silicon carbide or silicon nitride. These porous fired bodies are brittle materials and therefore easily broken by mechanical shock, etc. However, if the mat material 10 (holding seal material) is interposed around the side surface of the exhaust gas treatment body 120, the shock is absorbed, and therefore it is possible to prevent cracks, etc. from occurring in the exhaust gas treatment body 120 due to mechanical shock or thermal shock.

[0074] The exhaust gas treatment body may be supported with a catalyst for purifying the exhaust gas. The catalyst to be supported is preferably a precious metal such as platinum, palladium, or rhodium, and among these, platinum is more preferable. Other catalysts may also be used, such as an alkali metal such as potassium or sodium, or an alkaline earth metal such as barium. These catalysts may be used alone or in combination of two or more. When these catalysts are supported, PM can be easily burned and removed, and toxic exhaust gas can also be purified.

[0075] The exhaust gas treatment body constituting the exhaust gas purification device may be an integrally formed one-piece honeycomb structure made of cordierite or the like, or an aggregated honeycomb structure made of silicon carbide or the like and formed by bundling together a plurality of columnar honeycomb fired bodies having a large number of through holes arranged in parallel in the longitudinal direction separated by partitions via a paste mainly containing ceramic.

[0076] The exhaust gas treatment body constituting the exhaust gas purification device may not have a sealing material provided in the cells, and the ends of the cells may not be sealed. In this case, the exhaust gas treatment body supports a catalyst such as platinum, and functions as a catalyst carrier that purifies harmful gas components such as CO, HC, and NOx contained in the exhaust gas.

[0077] The holding seal material of the present invention made of the mat material of the present invention is used by being wrapped around an exhaust gas treating body. An example in which a wrapped body in which the holding seal material is wrapped around an exhaust gas treating body is disposed in an exhaust gas purifying apparatus will be described.

[0078] FIG. 9 is a perspective view that typically shows an example of a method for producing an exhaust gas purification device. 9, a holding and sealing material made of the mat material 10 is wound around the periphery of the exhaust gas treatment body 120 to form a wound body 140. Next, the wound body 140 is housed in a metal casing 130 to manufacture an exhaust gas purification device.

[0079] When preparing the wound body 140, the first main surface 23 of the laminated mat 20 constituting the mat material 10 is wound toward the exhaust gas treatment body 120. As a result, the first main surface 23 becomes the surface on the exhaust gas treatment body 120 side, and the second main surface 24 becomes the surface on the metal casing 130 side.

[0080] Next, methods of housing the wound body 140 in the metal casing 130 include, for example, a press-in method (stuffing method) in which the exhaust gas treatment body 120 (wound body 140) around which a retaining sealing material made of the mat material 10 is arranged is pressed into a predetermined position inside the metal casing 130, a sizing method (swaging type) in which the metal casing 130 is compressed from the outer periphery so as to reduce the inner diameter, and a clamshell method in which the metal casing is shaped so as to be separable into a first casing and a second casing, the wound body 140 is placed on the first casing, and then the second casing is placed over it to seal it. When the wound body is housed in the metal casing by the press-fitting method (stuffing method), it is desirable that the inner diameter of the metal casing (the inner diameter of the portion housing the exhaust gas treatment body) is slightly smaller than the outer diameter of the wound body. Through these steps, the wrapped body with the holding seal material wrapped around the exhaust gas treatment body can be placed in the exhaust gas purification device.

[0081] The present specification discloses the following:

[0082] The present disclosure (1) is a mat material comprising a laminated mat including at least one oriented layer made of inorganic fibers in which the orientation direction of the inorganic fibers is aligned, and at least one random layer made of inorganic fibers in which the orientation direction of the inorganic fibers is random, the laminated mat including a binder.

[0083] The present disclosure (2) is a mat material described in the present disclosure (1), in which the orientation layers and the random layers are laminated alternately in the thickness direction, and the random layers are arranged on both of the two outermost layers of the laminated mat.

[0084] The present disclosure (3) is the mat material according to the present disclosure (1) or (2), in which the laminated mat contains at least one of an organic binder and an inorganic binder.

[0085] The present disclosure (4) provides a method for manufacturing a laminated mat, the method comprising the steps of: dividing the laminated mat into three equal parts in the thickness direction into a first surface part, a central part, and a second surface part; and disposing the random layer on the outermost layer of the first surface part; The mat material according to any one of the present disclosures (1) to (3), wherein the binder content in the first surface portion is greater than the binder content in the central portion and greater than the binder content in the second surface portion.

[0086] The present disclosure (5) is the mat material according to the present disclosure (4), in which the content of the binder satisfies the following relationship. 0.4≦(center / first surface) 0.2≦(second surface portion / first surface portion) (Second surface / center)≦0.5

[0087] The present disclosure (6) is the mat material according to the present disclosure (5), in which the content of the binder further satisfies the following relationship. 0<(Second surface / center)

[0088] The present disclosure (7) is the mat material according to any one of the present disclosures (1) to (6), wherein the inorganic fibers in the orientation layer contain 70% or more of inorganic fibers having an inclination of 60 to 90 degrees with respect to the width direction of the mat material.

[0089] The present disclosure (8) is the mat material according to any one of the present disclosures (1) to (7), which has a tensile strength at break of 200 kPa or more as measured by a tensile test.

[0090] The present disclosure (9) is the mat material according to any one of the present disclosures (1) to (8), which has an elongation at break measured by a tensile test of 3.5 mm or less.

[0091] The present disclosure (10) is a holding sealer made of the mat material according to any one of the present disclosures (1) to (9), and used to hold an exhaust gas treatment body in an exhaust gas purification apparatus. EXAMPLES

[0092] Example 1 A papermaking mat was produced using a papermaking method, which consisted of inorganic fibers and had an oriented layer and a random layer. The mats were then laminated in the order of random layer / oriented layer / random layer / oriented layer / random layer, and then subjected to a needling process to produce a laminated mat.

[0093] A binder liquid containing an organic binder was applied to one main surface (random layer) of the laminated mat, and dried to prepare a mat material. The laminated mat was divided into three equal parts in the thickness direction, and the part including the random layer on the side where the binder liquid was applied was designated as the first surface part, and the part including the random layer on the opposite side to the side where the binder liquid was applied was designated as the second surface part. The part between the first surface part and the second surface part was designated as the center part. The binder content was determined from the change in weight before and after the application of the binder liquid. Table 1 shows the binder content ratio, which is the ratio of the binder content in two of the first surface portion, the central portion, and the second surface portion.

[0094] The photograph of the orientation layer is shown in Figure 4, and 52% of the inorganic fibers had an angle θ of 75 to 90 degrees. In addition, 78% of the inorganic fibers had an inclination of 60 to 90 degrees with respect to the width direction of the mat material. In the random layer photographed in the same manner as in Fig. 4, 14% of the inorganic fibers had an angle θ of 75 to 90 degrees, and 27% of the inorganic fibers had an inclination of 60 to 90 degrees with respect to the width direction of the mat material.

[0095] Comparative Example 1 A mat material (holding seal material) according to Example 1 of Patent Document 1 was prepared. The mat material of Example 1 of Patent Document 1 is not a laminated mat and does not have both an oriented layer and a random layer therein.

[0096] (Tensile test) The mat material was cut into a sample having a length of 200 mm along the longitudinal direction of the mat material and a width of 50 mm along the width direction of the mat material. The thickness of the sample was measured at three points, and using a universal testing machine equipped with a chuck (gripping jig) for tensile tests, the chuck distance was set to 40 mm on each side, and the mat material was pulled along the longitudinal direction of the sample at a speed of 100 mm / min. The load and pulling distance at the time of break were determined. The tensile strength at break was calculated as follows: (tensile strength at break) / (sample thickness×width). The tensile distance at break was taken as the elongation at break. The results are shown in Table 1.

[0097] [Table 1]

[0098] The results shown in Table 1 show that the mat material of Example 1 has high tensile strength. [Explanation of symbols]

[0099] 10 Mat material 20 Laminated Mat 23 First main surface of laminate mat 24 Second main surface of laminate mat 25 First long side of laminate mat 26 Second long side of laminate mat 27 First short side of laminate mat 28 Second short side of laminate mat 30 Alignment layer 31 Inorganic fibers constituting the orientation layer 40, 40a, 40b Random layer 41 Inorganic fibers that form random layers 50 Needle marks 51 Rivet section 100 Exhaust gas purification equipment 120 Exhaust gas treatment body 120a, 120b Exhaust gas inlet end surface 125 cells 126 Cell Wall 127 Outer coating layer 128 Encapsulating material 130 Metal Casing 140 Wrapped body

Claims

1. The laminated mat includes at least one layer each of an orientation layer made of inorganic fibers and having the inorganic fibers oriented in a uniform direction, and a random layer made of inorganic fibers and having the inorganic fibers oriented in a random direction, The laminate mat includes a binder, When the laminated mat is divided into three equal parts in the thickness direction into a first surface portion, a central portion, and a second surface portion, the random layer is disposed on the outermost layer of the first surface portion, A mat material, wherein the binder content in the first surface portion is greater than the binder content in the central portion and greater than the binder content in the second surface portion.

2. The mat material according to claim 1 , wherein the orientation layers and the random layers are alternately laminated in the thickness direction, and the random layers are disposed on both of the two outermost layers of the laminated mat.

3. 3. The mat material according to claim 1, wherein the binder is at least one of an organic binder and an inorganic binder.

4. The mat material according to claim 1 or 2, wherein the content of the binder satisfies the following relationship: 0.4≦(center portion / first surface portion) 0.2≦(second surface portion / first surface portion) (second surface portion / central portion)≦0.5

5. The mat material according to claim 4 , wherein the content of the binder further satisfies the following relationship: 0<(second surface portion / center portion)

6. 3. The mat material according to claim 1, wherein the inorganic fibers in the orientation layer contain 70% or more of inorganic fibers having an inclination of 60 to 90 degrees with respect to the width direction of the mat material.

7. 3. The mat material according to claim 1, which has a tensile strength at break of 200 kPa or more as measured by a tensile test.

8. 8. The mat material according to claim 7, which has an elongation at break measured by a tensile test of 3.5 mm or less.

9. A holding and sealing material comprising the mat material according to claim 1 or 2 and used for holding an exhaust gas treatment body in an exhaust gas purification apparatus.

Citation Information

Patent Citations

  • Holding member for catalytic converter

    JP1995102961A

  • Ceramic catalyst converter

    JP1998061433A

  • Holding seal material and exhaust gas treating device

    JP2007127112A

  • Sheet material, its manufacturing method, exhaust gas treating apparatus, and its manufacturing process

    JP2008080756A

  • Pollution control element mounting system and pollution control device

    JP2008506886A